ANALYSIS OF FOREIGN DEBT IN INDONESIA - Muhammad Refo Sayuti; Ichsan Ichsan; Khairil Anwar (Journal of Malikussaleh Public Economics, 2021)
This study aims to determine the short run and long-run effects of foreign exchange reserves, exports, and the dollar exchange rate on the foreign debts of Indonesia. This study uses time-series data during 1994-2020. The study employs the Autoregressive Distributed  Lag  (ARDL)  approach  with  the  help  of  Eviews  9. The results in the short-run equation model showed that the foreign exchange reserve had a positive and significant effect on the foreign debts of Indonesia, while exports and the exchange rate dollar has a positive but insignificant effect on the foreign debts of Indonesia. In the long run, the foreign exchange reserves and exports has a negative and insignificant effect on the foreign debts of Indonesia, while the dollar exchange rate has a positive but insignificant effect on Indonesia's foreign debt.